Eksplorasi Pengaruh Pandemi COVID-19 Terhadap Diagnostic Delay Dan Treatment Delay Pada Pasien Kanker Payudara - Melian, Ruella Rivenska; Rafli, Rhandyka; Maribeth, Annisa Lidra (PT. Riset Press International, 2024)
The COVID-19 pandemic has had an impact on health services for breast cancer patients. During the COVID-19 pandemic, there were new government regulations, namely PSBB or large-scale social restrictions. During the PSBB, activities in public facilities are limited to only urgent interests. Therefore, breast cancer patients have difficulties during examination and treatment during the COVID-19 pandemic. The obstacles for breast cancer patients are difficulties in mobilizing to the hospital, health protocol regulations such as maintaining distance, discomfort when wearing masks and swabs before treatment, the emergence of fear and anxiety, expensive transportation costs during examination and treatment, and psychological disorders. So the impact is delay in examination (diagnostic delay) and delay in treatment (treatment delay) of breast cancer patients. This study uses a qualitative descriptive method with an in-depth interview approach that is guided by semi-structured questions and triangulates the perspectives of patients, patients' families, and health workers. The study was conducted from November 2021 to August 2022. The sample used was 27 respondents by purposive sampling. Analysis using condensed text system. There are breast cancer patients who express fear of seeking treatment during the COVID-19 pandemic because of the increasing number of pandemic cases and the stigma of being